Icariin Research Trends: Bibliometric Analysis - Septiana Indratmoko; Laela Hayu Nurani; Iis Wahyuningsih; Rochany Septiyaninsih (Jurnal Penelitian Pendidikan IPA, 2023)
Icariin is a compound with various pharmacological effects, such as anti-osteoporosis, cardiovascular protection, anti-inflammatory, antitumor, immunoprotection, and sexual dysfunction improver. Over the past decades, several publications and literatures have studied the compound and its potential effects. This is a bibliometric analysis of academic studies related to icariin compounds, and their productivity. Therefore, this research aims to comprehensively analyse the findings of several articles related to icariin globally. The articles used were obtained from the Scopus database using the keywords "icariin" OR "icariine" OR "epimedii". Meanwhile, one of the inclusion criteria for the selection was articles published between 2010 and 2021. A total of 1,116 publications were then obtained from the search process, and the data were analyzed using VOSviewer, R-Studio (Biblioshiny). The results showed that the major contributing countries were China, South Korea, India, the United States, and Hong Kong, with a total of 844, 40, 26, 23, and 21 publications, respectively. Furthermore, the literatures were primarily published in pharmacology, chemistry, oncology, and biochemistry journals. The most mentioned compounds were icaritin, epimedium, flavonoids, icariside, and epimedin, which appeared in 41, 33, 29, 22 and 16 literatures, respectively. In the last 5 years, published research article focused on icariin’s effects on osteoporosis, inflammation, Alzheimer, oxidative stress, and osteoarthritis. Different formulation technologies, such as solid dispersion, liposomes, nanoparticles, microemulsion, cyclodextrin inclusion complex, self-microemulsifying drug delivery system, nanoemulsion, and pH-sensitive nanoparticles, have been explored.